Single Dose Intravenous Paracetamol versus Placebo in Postorthognathic Surgery Pain: A Randomized Clinical Trial - Thunshuda Sumphaongern; Pornchai Jansisyanont (Anesthesiology Research and Practice)
Background. The postorthognathic surgery patients experienced moderate to severe pain and could be at risk for opioid-related side effects. The aim of this study was to evaluate the efficacy of a single dose of intravenous paracetamol to control postorthognathic surgery pain and reduce opioid consumption. Methods. The patients were randomized into two groups. The study group received intravenous paracetamol and the control group received a placebo immediately postoperation. The visual analogue pain scale (VAS) at 1-, 4-, 8-, 12-, 16-, 20-, and 24 -h postoperatively, morphine consumption, side effects from morphine, and patient satisfaction were analyzed. Results. Sixty-two patients (thirty-one patients in each group) were included. The postoperative VAS in the study group was significantly lower than those in the control group (p value <0.001) at all time points. The total postoperative morphine consumption in the study group (45.1 ± 21.2 mcg/kg) was significantly lower compared with the control group (136.5 ± 49.9 mcg/kg) (p value <0.001). Patient satisfaction was significantly higher in the study group (4.7 ± 0.5 out of 5 points) than in the control group (4.1 ± 0.7 out of 5 points) (p value <0.001). The incidence of nausea and vomiting was significantly lower in the study group compared with the control group (p value <0.001 and 0.002, respectively). Conclusion. A single dose of intravenous paracetamol as part of multimodal analgesia was effective for postorthognathic surgery pain. It provided significant benefits to patients, including reduced pain scores, decreased opioid consumption, reduced nausea and vomiting, and improved satisfaction. This trial is registered with TCTR20210908002.